Kemampuan Menulis Puisi Melalui Transformasi Cerpen Kelas XI SMA Negeri 5 Pekanbaru - Yessy elvrina (Indonesian Journal of Educational Science (IJES), 2024)
This study aims to determine and describe the level of poetry writing ability through Malaikat Juga Tahu short story transformation of class XI SMA Negeri 5 Pekanbaru. This study was conducted at SMA Negeri 5 Pekanbaru with a sample of 80 class XI students. The duration of the study lasted for 10 days from 6 to 15 August 2024. The data collection methods used were observation and tests. Data analysis was carried out using descriptive statistical techniques. The ability to write poetry through short story transformation of class XI SMA Negeri 5 Pekanbaru was assessed based on five aspects, namely aspects of content suitability, typography, taste, language style and message. The typography aspect obtained the highest average score of 95,43 and the lowest average score of 72,61 was in the language style. The results of the data analysis obtained an average ability to write poetry through short story transformation of class XI SMA Negeri 5 Pekanbaru, namely 80,20%. It can be concluded that writing poetry through.